Dekalog dan Perjanjian yang Baru (Ul 5:6-21; Kel 20:1-17; Yer 31:31-34): The Decalogue and the New Covenant (Dt. 5:6-21; Ex. 20:1-17; Jr. 31:31-34) - Stanislaus, Surip (STF Driyarkara - Diskursus, 2022)
The Decalogue is the ten commandments which are a covenant between God and His people. Written on two tablets of stone, this Decalogue is apodictive (unconditional command and prohibition). It expresses the love between God and His people and between members of the people. This article shows that in the Pentateuch there are two versions of the Decalogue (Ex. 20:1-17 and Deut. 5:6-21) with some differences between them. Deuteronomy 5:6-21 contains additions to Exodus 20:1-17. Ex. 20:1-17 was spoken by God himself to the Israelites at Mount Sinai; Deut. 5:6-21 by Moses in the plains of Moab when quoting Ex. 20:1-17. The commandment to keep the Sabbath day holy in Ex. 20:8-11 is motivated by God’s rest on the seventh day of creation; in Deut. 5:12-15 it is motivated by Israel’s liberation from slavery in the land of Egypt. Ex. 20:13-17 contains fi ve social commandments in no apparent order; Deut. 5:17-21 contains six social commandments inparallel arrangement. The Decalogue, as a law does not guarantee its implementation. And the Israelites repeatedly violated or disobeyed the law. Therefore, God Himself takes the initiative and intervenes toensure its implementation. After the destruction of the city of Jerusalem as an outward sign of the end of the Old Covenant, the prophet Jeremiah prophesied the New Covenant at the initiative of God to bewritten in the hearts, so that previously impossible loyalty would now become a reality (Jer. 31:31-34). Thus, the New Covenant is not different from the Sinai Covenant, but rather a renewal of YHWH’s faithfulnesswhich is rebuilt and deepened continuously so that it becomes a “covenant without end” (Lam. 3:22-23). Abstrak Dekalog adalah sepuluh fi rman yang merupakan pernjanjian antara Allah dengan umat-Nya, tertulis dalam dua loh batu. Dekalog yang bersifat apodiktif (perintah dan larangan tanpa syarat) mengungkapkankasih antara Allah dengan umat-Nya dan antarumat Allah. Artikel ini menunjukkan bahwa dalam Pentateukh terdapat dua versi Dekalog (Kel. 20:1-17 dan Ul. 5:6-21) dengan beberapa perbedaan. Ul. 5:6-21 memuat beberapa tambahan yang tidak terdapat dalam Kel. 20:1-17. Kel. 20:1-17 diucapkan sendiri oleh YHWH kepada bangsa Israel di gunung Sinai; Ul. 5:6-21 diucapkan oleh Musa di dataran Moab dengan mengutip isi Kel. 20:1-17. Perintah kuduskanlah hari Sabat dalam Kel. 20:8-11 bermotifkan istirahat Allah pada hari ketujuh saat penciptaan; dalam Ul. 5:12-15 bermotifkan pembebasan bangsa Israel dari perbudakan di tanah Mesir. Kel. 20:13-17 memuat lima perintah sosial tanpa urutan yang jelas; Ul. 5:17-21 memuat enam perintah sosial yang disusun paralel. Dekalog sebagai undang-undang tidak menjamin pelaksanaannya. Berulangkali bangsa Israel telah melanggar atau tidak setia pada penjanjian tersebut. Maka, Allah sendiri yang berinisiatif dan campur tangan demi terjaminnya pelaksanaan perjanjian-Nya. Sesudah penghancuran kota Yerusalem sebagai tanda lahiriah berakhirnya Perjanjian Lama, Nabi Yeremia menubuatkan Perjanjian Yang Baru atas prakarsa Allah yang akan ditulis dalam hati manusia, sehingga kesetiaan yang tadinya mustahil akan menjadi kenyataan (Yer. 31:31-34). Dengan demikian Perjanjian Yang Baru itu tidak berbeda dengan Perjanjian Sinai, tetapi lebih berupa pembaruan kesetiaan YHWH yang dibangun kembali dan diperdalam terus-menerus sehingga menjadi “perjanjian yang tak berkesudahan” (Rat. 3:22-23).